Impacts of Logging-Associated Compaction on Forest Soils: A Meta-Analysis - Nazari, Meisam; Eteghadipour, Mohammad; Zarebanadkouki, Mohsen; Ghorbani, Mohammad; Dippold, Michaela A.; Bilyera, Nataliya; Zamanian, Kazem (Frontiers in Forests and Global Change, 2021)
Soil compaction associated with mechanized wood harvesting can long-lastingly or irreversibly damage forest soils, ecosystem function, and productivity. Sustainable forest management requires precise and deep knowledge of logging operation impacts on forest soils, which can be attained by meta-analysis studies covering representative forest datasets. We performed a meta-analysis on the impact of logging-associated compaction on forest soils microbial biomass carbon (MBC), bulk density, total porosity, and saturated hydraulic conductivity (Ksat) affected by two management factors (machine weight and passage frequency), two soil factors (texture and depth), and the time passed since the compaction event. Compaction significantly decreased soil MBC by -29.5% only in subsoils (>30 cm). Overall, compaction increased soil bulk density by 8.9% and reduced total porosity and Ksat by -10.6% and -40.2%, respectively. The most striking finding of this meta-analysis is that the greatest disturbance to soil bulk density, total porosity, and Ksat occur after very frequent (>20) machine passages. This contradicts the existing claims that most damage to forest soils happens after a few machine passages. Furthermore, the analyzed physical variables did not recover to the normal level within a period of 3-6 years. Thus, altering these physical properties can long-lastingly disturb forest ecosystem function and productivity, because they play important roles in water and air supply as well as in biogeochemical cycling in forest ecosystems. To minimize the impact, we recommend the selection of suitable logging machines and decreasing the frequency of machine passages as well as logging out of rainy seasons especially in clayey soils. It is also very important to minimize total skid trail coverage for sustainable forest management.